Implant orientation accuracy of a hand-held robotic partial knee replacement system over conventional technique in a cadaveric test. Issue 1 (1st January 2018) - Khare, Rahul; Jaramaz, Branislav; Hamlin, Brian; Urish, Kenneth L.
Abstract: Unicondylar Knee Arthroplasty (UKA) is a minimally-invasive surgical procedure for treating isolated compartmental knee osteoarthritis. Accurate implant placement is crucial for a successful UKA procedure. Previous work has shown the improvement in UKA by using robotic systems. Here, we present the implant alignment accuracy of a hand-held robotic UKA system compared with a conventional manual UKA system for 12 cadaver specimens. Two surgeons carried out equal number of medial UKAs with robotic UKA on one knee and the manual UKA on the other knee. Preoperative and postoperative computed tomography (CT) scans were obtained for each cadaveric model. The final implant positions were identified in the postoperative CT scan. The implant orientations were compared with the planned implant positions to obtain femoral and tibial implant alignment errors. Our results show that the femoral flexion, varus, and rotation root mean square errors for the robotic and conventional approach were 1.23°, 2.81°, 1.62° and 7.52°, 6.25°, 5.0°, respectively. The tibial slope and varus errors for the robotic and conventional approaches were 2.41°, 2.96° and 4.06°, 1.8°, respectively. We did not find any statistical significant difference ( p  = .05) in the performance of the two surgeons. We conclude that the hand-held robotic UKA system offers significant improvement in the final implant placement